3PC-048 Oral mucoadhesive dexamethasone 0.1% (m/m) gel: a strategy for motor inhibitors mucositis. (March 2019) - Cosme Silva, AF; Castro, A; Ferreira, A; Luna Pais, H; Rodrigues, V; Cruz, JP; Duarte, A; Simões, S; Eleuterio, C; Almeida, AJ; Marto, J
Abstract : Background: Stomatitis is the most referred adverse reaction during everolimus treatment (in metastatic breast cancer). In a post-commercial study (n=92) the prophylactic administration of an oral solution of dexamethasone resulted in an important reduction in incidence and severity of stomatitis. In Portugal, there is not any formulation on the market that permits a topical administration of dexamethasone. Purpose: Development, characterisation and stability studies of a new oral mucoadhesive gel of dexamethasone (DEX) at 0.1% (m/m) for prophylaxis/treatment of oral mucositis with an effective topic action, good palatability and ease of use by our patients. Material and methods: A gel was developed without sucrose to obtain chemical and physical properties suitable for the administration, storage and therapeutic compliance. Full pharmaceutical quality testing was carried out (rheology and adhesion tests). Appropriate stability-indicating analytical methodology was developed to quantify DEX. The microbiological and stability tests were performed during 180 days. The in vitro release study of DEX was performed by using Franz diffusion cells. An observational study of its clinical use are still ongoing. Results: A stable formulation of gel was obtained with a period of use of 180 days at 25°C±3°C. The compounded product has suitable pharmaceutical characteristics, such as rheology, in vitro release profile and a pH value suitable for oral administration. Its clinical application in a patient with grade 3 mucositis resulted in excellent acceptability and significant reduction in the degree of mucositis (for grade I) and re-introduction of EVR into the therapeutic regimen at the end of a week of treatment with the gel. Conclusion: This mucoadhesive gel can be an effective option for the prophylaxis/treatment of oral mucositis, for its prolonged residence time in the oral cavity and easier administration. The pleasant taste promotes a good therapeutic compliance, as well as the smooth and suitable texture for the treatment of an aggressive mucosa. The inclusion of more patients in this study will validate these assumptions. Reference and/or acknowledgements: Rugo HS, et al. Prevention of everolimus-related stomatitis in women with hormone receptor-positive, HER2-negative metastatic breast cancer using dexamethasone mouthwash (SWISH): a single-arm, phase 2 trial. Lancet Oncol [Internet] Elsevier Ltd; 2017;18:654–62. No conflict of interest.